Restricted nitrous oxide emissions by ammonia oxidizers in two agricultural soils following excessive urea fertilization - Chen, Zhaoming; Wang, Qiang; Zhao, Jun; Chen, Yudong; Wang, Huoyan; Ma, Junwei; Zou, Ping; Bao, Li (Journal of soils and sediments, 2020)
Purpose Nitrogen (N) fertilizer placement in bands is a widely accepted agricultural practice to increase N use efficiency. An excessive ammonium concentration in a fertilizer band can increase osmotic stress on ammonia oxidizers and potentially affect nitrification and resultant nitrous oxide (N 2 O) emissions, which is of great significance for soil function and climate change. The objectivity of this study was to identify the effects of excessive ammonium concentration on N 2 O emissions and ammonia oxidizers in two agricultural soils. Materials and methods In this study, we established a 56-day soil microcosm receiving a series of high concentrations of urea at 600, 900, and 1200 mg N kg −1 (termed as N600, N900, and N1200, respectively), which simulated high ammonium levels in the center or proximity of a fertilizer band in two types of agricultural soils (fluvo-aquic soil and anthrosol). The mineral N concentrations, net nitrification rate, and N 2 O emissions were measured during the incubation. In addition, the abundances of bacterial and archaeal amoA were determined by using real-time quantitative PCR. Results and discussion Urea fertilization simultaneously increased the net nitrification rate and N 2 O emission at the early stage of incubation in both soils, suggesting N 2 O production was mainly from ammonia oxidation. Ammonia oxidizing bacteria (AOB) but not archaea (AOA) abundance was stimulated following urea fertilization and was positively correlated with N 2 O emission, indicating the dominant role of AOB in ammonia oxidation and N 2 O production in fertilized soils. The cumulative N 2 O emission was significantly higher in N1200 and N900 than N600 in both soils, but no further increase was observed in N1200 in the anthrosol. This implies restricted N 2 O production of ammonia oxidizers at excessive ammonium concentrations in the anthrosol. In the two soils treated with no N addition, the abundances of AOA amoA increased along the incubation time. Conclusions The present study collectively suggested that excessive urea-N addition was more effective in inhibiting N 2 O emission in the anthrosol than in the fluvo-aquci soil. AOB rather than AOA dominated the soil nitrification and N 2 O emissions under high N addition in both soils. The band fertilization regime may reduce the loss of N fertilizer from nitrification without necessarily increasing N 2 O emissions.